La guerra d’Algeria (1954-1962) al cinema in 14 film (1961-2011) - Rosselli, Alessandro (Études sur la Région Méditerranéenne, 2022)
This article wants only to present an imperfect panorama on what the cinema have produced on the Algerian war (1954–1962). The cinema haven’t done a great number of film on this topic, but a very interesting series of movies into 1961 and 2011. The films, above all frenchs and italians, except Les centurions (or The lost command, known in Italy as Né onore né Gloria, 1966) by Mark Robson, a French-American co-production, have reported the methods used by the French army to reprime the Algerian rebellion of the F.L.N., including torture, but too all the French ambiguities on this vain and colonialist war in delay during the time.